Ethics in the New Testament Personal Relationship with God and Holiness Ethics: An Exploration of Issues in Revelation 21:3 and Revelation 21:22 - Sitorus, Herowati (the International Journal of Education, Theology, and Humanities, 2024)
This article explores the ethics of holiness in the context of a personal relationship with God, as described in Revelation 21:3 and 21:22. In these verses, the emphasis on God's presence amid His people highlights the importance of the intimate relationship between man and the Creator. This research analyzes how the ethics of holiness not only serve as a moral guide but also as a consequence of a deep relationship with God. Ethics in the context of the New Testament, especially in the Book of Revelation, offers deep insight into the relationship between man and God. Revelation 21:3 and 21:22 serve as the culmination of eschatological hope, presenting the ultimate vision in which God dwells among His people. Through these two verses, we can explore how divine presence affects ethical norms and human behaviour. Through a hermeneutic approach and text analysis, this article discusses the implications of God's closeness to His people, including the ethical responsibilities that arise from such relationships. Additionally, this article considers contemporary challenges in applying holiness ethics in everyday life, as well as how these values can guide individuals to live in holiness and integrity. The conclusions of this study suggest that a deeper understanding of personal relationships with God can increase an individual's ethical awareness, strengthen a commitment to holy living, and encourage communities to create an atmosphere that reflects the values of God's Kingdom. As a result, the narrative of the restoration of the cosmic order of Christianity is not much different from the narrative of the times. But in the light of redemptive history, the tabernacle of God affirms the final expansion of Eden, the revelation of God's glory, and His fellowship with man. Therefore, a good and meaningful portrait of human life should be by the purpose of creation.